Evaluasi penyusunan laporan pertanggungjawaban bendahara pengeluaran pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Manado - Worang, Flowerentie Orelia; Kalangi, Lintje; Wokas, Heince R. N. (Yayasan Widyantara Nawasena Raharja, 2025)
The position of Treasurer, which is part of the Regional Finance Management Task Unit (SKPKD) and regional work units (SKPD), is responsible for receiving, recording, storing, disbursing funds, and managing goods, as well as being accountable to the regional head (the budget authority). This study aims to examine and evaluate the administration and preparation of the expenditure treasurer’s accountability report at the Manado City Personnel and Human Resources Development Agency. The research employs a qualitative descriptive method. The findings indicate that the administration and preparation of the expenditure treasurer’s accountability report at the Manado City Personnel and Human Resources Development Agency comply with Minister of Home Affairs Regulation Number 77 of 2020 concerning Technical Guidelines for Regional Financial Management.